Design of low phase-noise oscillators based on microstrip triple-band bandpass filter using coupled lines resonator. (January 2019) - Khamin-Hamedani, Farnaz; Karimi, Gholamreza
Abstract: This paper presents new low phase noise oscillators employing a triple-band bandpass filter as a frequency stabilization element into the feedback loop. In addition, using triple-band bandpass filter (TB-BPF); three oscillators can be easily achieved separately, only by changing the length of the transmission line in feedback loop. The oscillators are designed at the spectrum-based quality factor (Qs ) peak frequencies of bandpass filter to achieve low phase noise performance. Also, the oscillation frequencies of the oscillators are designed at 3.4, 4.33 and 6.89 GHz, resulting in achieving the simulated phase noise of these oscillators are −166, −154 and −150 dBc/Hz at the 1-MHz offset frequency respectively. The oscillator with 3.4 GHz carrier frequency is fabricated and the measured results show the 10.7 dBm output power and phase noise is −163 dBc/Hz at 1-MHz frequency offset. The figure of merit of the fabricated oscillator at 1 MHz offset frequency is −218.9 dBc/Hz.